1978
DOI: 10.1097/00000658-197807000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Injury-An Increasing Problem

Abstract: Inhalation injury is a common complication of thermal accidents occurring in one-third of patients burned. The routine use of fiberoptic bronchoscopy on all patients incurring thermal burns provides an accurate and safe means for diagnosis. Although complications for inhalation injury are common, the mortality can be reduced by early diagnosis and attention to careful fluid resuscitation, aggressive pulmonary therapy and the avoidance of prophylatic steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Both the onset and the severity of airway oedema are difficult to predict accurately, and we know surprisingly little of the natural history of airway pathology following thermal injury [9,10]. Thermal injury to the oral cavity and throat can cause oedema; with severe injury, airway obstruction may result as a consequence of oedema of the supraglottic airway and, in particular, the false vocal cords [11]. In many cases, clinically significant obstruction only occurs following fluid resuscitation, with maximal oedema typically presenting 8-36 h after the initial insult, and lasting for up to four days [5,11,12].…”
Section: Pathophysiology Of Airway Burnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the onset and the severity of airway oedema are difficult to predict accurately, and we know surprisingly little of the natural history of airway pathology following thermal injury [9,10]. Thermal injury to the oral cavity and throat can cause oedema; with severe injury, airway obstruction may result as a consequence of oedema of the supraglottic airway and, in particular, the false vocal cords [11]. In many cases, clinically significant obstruction only occurs following fluid resuscitation, with maximal oedema typically presenting 8-36 h after the initial insult, and lasting for up to four days [5,11,12].…”
Section: Pathophysiology Of Airway Burnsmentioning
confidence: 99%
“…Clinical signs such as facial burns, hoarseness, drooling, carbonaceous sputum and singed nasal hairs raise the possibility of airway involvement, but they are unreliable and poor predictors of injury severity [1,11,[17][18][19]. Reliance on these signs may also lead to patients with clinically significant airway involvement going undetected [18,19].…”
Section: Determining the Need For Tracheal Intubationmentioning
confidence: 99%
“…Reduced lung function and symptoms resembling those in industrial bronchitis have been found in firemen who have inhaled smoke.7 Little is known, however, about the long term effects of smoke inhalational injury, which is probably underreported. 8 What is known about the acute effects is that inhalation of smoke increases mortality from serious burns and, by incapacitating people, slows down the rate of escape from fires. The aisles and exits of aeroplanes are narrow, and it takes few bodies to block them.…”
Section: Smoke Hoods In Aeroplanesmentioning
confidence: 99%
“…Although some authors have advocated prophylactic corticosteroid therapy to reduce parenchymal inflammation and subsequent fibrosis [28], others have noted increased infectious complications with their use [4,27]. Although some authors have advocated prophylactic corticosteroid therapy to reduce parenchymal inflammation and subsequent fibrosis [28], others have noted increased infectious complications with their use [4,27].…”
Section: Table 2 Action Criteria For Toxic Inhalationsmentioning
confidence: 99%